2021
DOI: 10.35848/1882-0786/abebf4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of ferroelectricity in hafnium–zirconium dioxide films deposited by sputtering and chemical solution deposition for oxide-channel ferroelectric-gate transistor applications

Abstract: Stability of ferroelectricity in hafnium–zirconium oxide (HZO) films deposited by sputtering and chemical solution deposition (CSD) has been investigated. After confirming the ferroelectricity of both sputtered HZO and CSD yttrium-doped HZO (Y-HZO) films, indium-tin-oxide (ITO) was deposited by sputtering on sputtered HZO or CSD Y-HZO layer to fabricate metal-ferroelectric-semiconductor (MFS) structure. It was found that the sputtered HZO films in the MFS structure became paraelectric after re-annealing in N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…When the sputtered HZO film was crystallized in N 2 , it usually has both o/c/t and monoclinic (m) phases. 23) On the other hand, Fig. 3(b) shows the m-phase peak around 28.5°is negligible for the HZO film with Cat-H treatment, which was crystallized in N 2 and air.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…When the sputtered HZO film was crystallized in N 2 , it usually has both o/c/t and monoclinic (m) phases. 23) On the other hand, Fig. 3(b) shows the m-phase peak around 28.5°is negligible for the HZO film with Cat-H treatment, which was crystallized in N 2 and air.…”
Section: Resultsmentioning
confidence: 92%
“…The remanent polarization is as large as 20 μC cm −2 for the HZO film without the Cat-H treatment, whereas the 30 min Cat-H treated HZO film shows higher remanent polarization of 24 μC cm −2 . Since the stability of the ferroelectric o-phase is a concern in the sputtered HZO films especially for device applications, 23) next we examined the stability of reduced pressure annealed HZO films with and without the Cat-H treatment. The samples were re-annealed at 400 °C for 15 min in N 2 with Pt electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previously reported results for an MFS structure with a sputtered ferroelectric HZO, which revealed that the ferroelectric properties were easily degraded by an additional O 2 annealing process. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…We applied the film to fabricate Pt/La-HZO/ITO/Pt metal-ferroelectric-semiconductor (MFS) structures to evaluate the stability of the o-phase because we found that the 8 at% La-HZO films annealed at 800 °C possessed good ferroelectric properties for the MFM structure. [23,24] We deposited a thin ITO layer by performing CSD on the La-HZO layer; it was crystallized at 800 °C. The CSD ITO channel layer was annealed at 600 °C in a N 2 or O 2 atmosphere.…”
Section: Electrical Properties Of Metal-ferroelectric-semiconductor S...mentioning
confidence: 99%